Between Two Line Follower Stand Before the Barrier Mobile Robot-Design and Implementation - Abdülkadir Çakir; Amal Ali Sreawi (Institute of Advanced Engineering and Science, 2017)
A Between two line follower stand before the barrier mobile robot is a mobile machine that can detect and follow between two line drawn on the floor. Generally, the path can be white lines on a black surface or it can be black lines on a white surface. Today robot is very important in our life because it can do everything without human intervention, especially for difficult or danger works. Therefore in this research we will going to design robot that able to walk between two lines, and at the same time, this robot can pass the barriers that facing it. We conclude from this that this robot can help in many areas, such as to be a helper in hazardous work or in the transport of materials that are dangerous to human life, Or that this robot be helpful for people with disabilities where carts industry able to navigate seamlessly, also can use this robot in military actions.